Desenvolvimento de luminária com espectro dedicado para suplementação luminosa no cultivo de flores - Grazziotin, Nathália (2024)
Light-emitting diode technology (LED) is continually expanding. In addition to its already established use in residential, industrial, and public lighting, it is widely applied in agriculture in controlled environments to replace or complement sunlight. Among its potential applications in horticulture, artificial lighting with LED systems can occur in growth chambers, greenhouses, multi-layer vertical cultivation and open fields. This work proposes designing, developing, and evaluating of energy-efficient luminaires with dedicated light spectra, applied as supplementary lighting in the open-field cultivation of statice and sunflower species. The research is based on scientific references that discuss the topic, covering a review of the importance of light in all phases of plant development, the effects induced by different light spectra, the relevant photometric parameters in horticultural lighting, the selected light spectra, and a detailed description of the experimental field trials conducted in 2023 in a planting area provided by the Federal University of Santa Maria, in partnership with the Phenoglad team. Each experiment in this study involved a comparative analysis between the experimental results obtained and data from controls without lighting, focusing on observing the effects of the proposed light spectra. Photometric, illuminance, electrical, and thermal tests were carried out to validate the spectroscopic effectiveness, providing a robust foundation for effectively implementing the developed lighting systems. Based on the analysis of the experimental results, it is concluded that there is no single light spectrum that can be universally applied in horticulture as a complement to sunlight. Therefore, an energy-efficient luminaire equipped with an adaptable spectrum was developed. This approach offers the ability to customize light spectra, allowing precise adaptation to the specific needs of each plant species, providing an adaptive and flexible solution with the potential to optimize the efficiency of the photosynthetic process and positively influence plant growth and development parameters.